Русская драматургия XIX века - Никулин Сергей Константинович (Современник, 1988)
Экземпляры: Аб (20120125) / Инвентарный номер: 97921 / Цена: 10.00 / Авт.знак: Р 89 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1